Oxidation Resistance and Modification Reaction Mechanism of Al Coating Sprayed on Pure Ti Substrate - Qianqian Jia; Deyuan Li; Sheng Guan; Zhuang Zhang; Nannan Zhang; Wenzhen Zhao (Advances in Materials Science and Engineering)
An Al coating was deposited on the surface of pure Ti substrate by arc spray technology. In order to enable the modification reaction between the Al coating and Ti substrate, the specimen was heated to a temperature above the melting point of Al. Oxidation testing of the uncoated Ti and coated specimen was conducted at 1073 K under an air atmosphere. The microstructure, chemical composition, and phase determination of the coatings and interfaces, before and after modification treatment, were done using SEM, EDS, and XRD methods. The relationships between the modification results and time and temperature were discussed. The results showed that, after heating at 973 K for 5 hours, there was still sufficient Al on the surface of the specimen. Only intermetallic TiAl3 was formed in the diffusion region. After heating at 1073 K for 5 hours, all the Al elements diffused into the Ti substrate. Intermetallics TiAl2 and Ti3Al were also formed in the diffusion front of Al, in addition to TiAl3. After heating at 1173 K for 5 hours, a new intermetallic TiAl phase was formed at the interface of TiAl2 and Ti3Al. As the modification reaction time was prolonged at 1173 K, the formation of intermetallics TiAl2, TiAl, and Ti3Al were all increased. Among them, the formation amount of TiAl2 > Ti3Al > TiAl. The specimen after modification treatment had better high temperature oxidation resistance than the pure Ti substrate without coating.